Recognition of food antigens by the mucosal and systemic immune system: Consequences for intestinal development and homeostasis - Yasmina Rodriguez-Sillke; Alexander Visekruna; Rainer Glauben; Britta Siegmund; Ulrich Steinhoff (Elsevier, 2021)
The impact of nutrition on systemic and intestinal immune responses remains controversially discussed and yet not fully understood. The majority of studies investigating the effects of dietary antigens focused to understand how local and systemic unresponsiveness is induced by innocuous food antigens. Moreover, it has been shown that both, microbial and dietary antigens are essential for the normal development of the mucosal immune system. Based on experimental findings from animals and IBD patients, we propose a model how the intestinal immune system performs the balancing act between recognition and tolerance of dietary antigens at the same time: In the healthy gut, repetitive uptake of dietary antigens by Peyer's patches leads to increasing activation of CD4+ T cells till hyper-activated lymphocytes undergo apoptosis. In contrast to healthy controls, this mechanism was disturbed in Crohn's disease patients. This observation might help to better understand beneficial effects of dietary intervention therapy.